Comparison of Risk Factors for Postoperative Complications Across Age Groups in Patients Undergoing ORIF of the Ankle. Issue 4 (16th October 2019) - McKissack, Haley; Anderson, Matthew; Wilson, John T.; Moraes, Leonardo V. M.; Viner, Gean C.; Jha, Aaradhana. J.; Buddemeyer, Katherine; Jones, James R.; McGwin, Gerald; Shah, Ashish B.
Category: Ankle, Trauma Introduction/Purpose: Ankle fractures are commonly-seen orthopaedic injuries across all age groups, and often warrant operative management. Postoperative complications are particularly common among elderly patients, and can lead to a progressive culmination of negative outcomes. Although several studies have focused on the risk factors for and prevention of such complications in elderly patients, a paucity of literature exists addressing risk of postoperative complications in younger patient populations. The purpose of this study was to compare the incidence of and risk factors for various postoperative complications between younger and older patient populations. Methods: Patients who underwent open reduction and internal fixation for an ankle fracture at a single institution between the years 2008 and 2018 were retrospectively identified based on seven different Current Procedural Terminology (CPT) codes: 27829, 27784, 27822, 27814, 27769, 27792, and 27766. Patient charts were reviewed for demographic data and comorbid conditions. Patients with open fractures, pilon fractures, and polytraumatic injuries were excluded. The sample was stratified into two cohorts based on age in years: 18-49 (group 1), and 50 and older (group 2). Incidence of various postoperative complications—including infection, wound dehiscence, sepsis, DVT, implant failure, revision surgery, and non-union— was compared between groups. Secondary analysis was conducted to compare risk factors for these complications between ages 18- 49 and older than 50. Results: 881 patients were included. A significantly greater number of patients in group 2 experienced wound dehiscence (p = 0.033) and nonunion (p<0.001) postoperatively in comparison to those in group 1. Risk of infection was significantly increased among patients with hypertension, CHF, and CKD compared to patients without these comorbidities in both group 1 and group 2. Risk of wound dehiscence was significantly increased among patients using tobacco and illicit drugs in group 1 (RR=3.39, p=0.0223 and RR=3.07, p=0.0201 respectively), but not in group 2 (RR = 1.12, p = 0.8021 and RR = 1.77, p = 0.4203 respectively). Risk of implant failure was significantly increased among tobacco users in group 2 (RR=3.82, p = 0.0005), but not in group 1 (RR = 0.75, p=0.4709). Conclusion: Patients age 50 and older may be at significantly increased risk for postoperative wound dehiscence and nonunion in comparison to patients who are younger than 50. Additionally, younger patients who use tobacco and illicit drugs may be at increased risk of wound dehiscence, while tobacco use among patients 50 years and older may increase risk of implant failure. Understanding the risk factors associated with negative outcomes may help physicians to optimize individual patient care based on existing comorbidities and age.